Anatomical study of some Silene L. species of Lasiostemones Boiss. section in Iran - Keshavarzi, Maryam; Mahdavinejad, M.; Sheidai, Masoud; Gholipour, Abbas (Acta Biologica Szegediensis, 2014)
Silene (Caryophyllaceae) composed of 110 species in Iran from which 35 species are endemic. Lasiostemones section is one of Silene sections with 10 species in Iran. In present study leaf and stem anatomical structure were considered for the first time. In order to study the anatomical variations of stem and leaf, 36 populations of 7 species of Silene (Lasiostemonessection) were collected from different habitats of Iran. In leaf anatomy vascular bundle shape, shape of dorsal surface of mid vein, cortex diameter, hair presence in dorsal and ventral surface of leaf, mid rib diameter, cuticle upper and lower thickness, fiber presence in mid rib, stomata cell shape, stomata index and hair frequency show significant differences among studied species. In stem anatomy features as shape of cross section, hair type, cortex and xylem and phloem diameter were of diagnostic value in species separation.